Lipid Droplet Surface Promotes 3D Morphological Evolution of Non‐Rhomboidal Cholesterol Crystals - Hyun‐Ro Lee; Seunghan Kang; Siyoung Q. Choi (Advanced Science)
Abstract Cholesterol crystals, which cause inflammation and various diseases, predominantly grow in a platy, rhomboid structure on the plasma membranes but exhibit an uneven three‐dimensional (3D) architecture intracellularly. Here, it is demonstrated how cholesterol crystallizes in a non‐rhomboidal shape on the surface of lipid droplets and develops into 3D sheet‐like agglomerates using an in vitro lipid droplet reconstitution system with stereoscopic fluorescence imaging. The findings reveal that interfacial cholesterol transport on the lipid droplet surface and unique lipid droplet components significantly influence the nucleation‐and‐growth dynamics of cholesterol crystals, leading to crystal growth in various polygonal shapes. Furthermore, cholesterol crystals readily agglomerate to form large, curved sheet structures on the confined, spherical surfaces of lipid droplets. This discovery enhances the understanding of the volumetric morphological growth of intracellular cholesterol crystals.